ANALISIS KESADARAN DIRI MAHASISWA AKAN KEBERSIHAN LINGKUNGAN KAMPUS STKIP MUHAMMADIYAH SAMPIT - Rabiatul Anisah; Apuanor Apuanor; Sudarmono Sudarmono (STKIP MUHAMMADIYAH SAMPIT, 2018)
This research was conducted to find out how students' self awareness of the cleanliness of campus environment in STKIP Muhammadiyah Sampit Academic Year 2016/2017. The population in this study is all students of STKIP Muhammadiyah Sampit amounting to 412 students Academic Year 2016/2017. The sampling technique used is a random sample technique or a random sample where the sample amounted to 206 students. Researchers use this technique because the population in the study exceeds 100. The data analysis technique used is descriptive quantitative. Based on the result of the research, most of the students who have high category as many as 29 respondents (14.07%) consisting of 6 male respondents and 23 female respondents, for the medium category are 146 respondents (70.87%) consisting of 39 respondents Men and 107 female respondents, and for the low category of 31 respondents (15.04%) consisting of 7 male respondents and 24 female respondents.